Compensation systems attributes and teachers' performance: mediating effect of psychological contract fulfilment. (13th August 2019) - Idrees, Rana Nadir; Naqvi, Imran Haider; Imran, Asma; Ismail, Muhammad
Higher education institutions (HEIs) play a role in building a knowledge economy, but doing so requires dedicated, well-educated and well-performing teachers, so teachers' performance (TP) has become an issue for developing countries. This research evaluates the impact of compensation system schemes on teachers' performance in the universities of Pakistan in order to explain the mediating role of psychological contract fulfilment (PCF). A nationwide survey of 52 HEIs in Pakistan was conducted using the random sampling probability technique. After the data collection, mediation was checked using quantitative research methods, including correlation, regression, multiple mediation, and process. This study analyses the importance of psychological contract fulfilment in mediating the relationship between compensation systems attributes (CSAs) and teachers' performance and suggests that psychological contract fulfilment mediates the relationship between compensation system attributes and teachers' performance. This study confirms and extends existing empirical evidence concerning the basis of the CSAs-PCF-TP relationships. The current study helps higher-education authorities and other policymakers to realign their compensation systems to create stronger relationships between compensation and psychological contract fulfilment to teacher's performance, which will help them to attain their sustainable development plans.